Spiritual mapping in the United States and Argentina, 1989-2005 : a geography of fear - Holvast, René. (Religion in the Americas, 2009)
Spiritual Mapping is a U.S. Evangelical and Neo-Pentecostal movement (1989-2005), which developed its own religious technique to wage a 'spiritual' war against unseen non-human beings. These 'spirits' were identified along the lines of geographical territories and put on a map, whence 'Spiritual Mapping' . Its intended function was to boost the numerical growth of Christianity. This book offers a comprehensive historical-descriptive approach of both the movement and the concept, with special attention for theological and anthropological concepts. Its historical roots, relation with Argentina, self-understanding and critics are being described. The reader is presented with a unique insight into Spiritual Mapping as an expression of Americanism, as well as the socio-political concept of Manifest Destiny and U.S. religious marketing.